Ketamine Does Not Exert Protective Properties on Dopaminergic Neurons in the Lactacystin Mouse Model of Parkinson’s Disease - Deneyer, Lauren (Front Behav Neurosci, 2018)
Parkinson’s disease (PD) is an age-related neurodegenerative condition characterized by a progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). A loss of proteasome function participates to the pathogenesis of PD, leading to the development of rodent models in which a proteasome inhibitor is applied to the nigrostriatal pathway. We recently characterized the intranigral lactacystin (LAC) mouse model, leading to nigrostriatal degeneration, motor dysfunction and alpha-synuclein accumulation. In the present study, we compared the effect of two commonly used anesthetics for generating animal models of PD—i.e., ketamine (KET) and isoflurane (ISO)—on the vulnerability of mouse dopaminergic neurons to proteasome inhibition-induced degeneration. Both anesthetics have the potential to affect the susceptibility of the nigrostriatal pathway for toxin-induced degeneration, and are known to modulate dopamine (DA) homeostasis. Yet, their impact on nigrostriatal degeneration in the proteasome inhibition model has not been evaluated. Unilateral injection with LAC in the SNpc of mice induced motor impairment and significantly reduced the number of dopaminergic cells to ~55%, irrespective of the anesthetic used. However, LAC-induced striatal DA depletion was slightly affected by the choice of anesthetic, resulting in a significant increase in DA turnover in the ISO- but not in KET-treated mice. These results suggest that the extent of nigrostriatal dopaminergic neural loss caused by LAC is not influenced by the choice of anesthetic, and that compared to other PD models, KET is not neuroprotective in the LAC model.